Age Is a Greater Influence on Small Saccades Than Target Size in Normal Subjects on the Horizontal Video Head Impulse Test - Jay, David R.; Cane, Debbie; Howe, Simon (Frontiers in Neurology, 2019)
Objective: This study sought to investigate whether the size of the target used in the horizontal vHIT has an effect on the saccade profile of healthy subjects, and to expand upon previous work linking age to the existence of small vHIT saccades. Methods: 48 participants were recruited between 18 and 77 years of age, with no history of vestibular, oculomotor or neurological conditions and a visual acuity of at least 0.3 LogMAR. Participants underwent four consecutive horizontal vHIT trials using the standard target size and three smaller targets. VOR gain and metrics for saccadic incidence, peak eye velocity and latency were then extracted from results. Results: Target size was a statistically significant influence on saccade metrics. As target size increased, saccadic incidence decreased while peak eye velocity and latency increased. However, a potential order effect was also discovered, and once this was corrected for the remaining effect of target size was small and is likely clinically insignificant. The effect of age was much stronger than target size; increasing age was strongly positively correlated with saccadic incidence and showed a medium size correlation with peak velocity, though not with saccadic latency. Conclusion: While this study suggests that target size may have a statistically significant impact on the vHIT saccade profile of normal subjects, age has a greater influence on the incidence and size of small vHIT saccades.